Targeting coenzyme Q10 synthesis overcomes bortezomib resistance in multiple myeloma. (26th August 2021) - Zaal, Esther A.; de Grooth, Harm-Jan; Oudaert, Inge; Langerhorst, Pieter; Levantovsky, Sophie; van Slobbe, Gijs J. J.; Jansen, Jeroen W. A.; Menu, Eline; Wu, Wei; Berkers, Celia R.
Abstract : This study links CoQ synthesis to bortezomib resistance in multiple myeloma and provides a novel avenue for improving BTZ response through statin-induced inhibition of mitochondrial metabolism. Abstract : During the development of drug resistance, multiple myeloma (MM) cells undergo changes to their metabolism. However, how these metabolic changes can be exploited to improve treatment efficacy is not known. Here we demonstrate that targeting coenzyme Q10 (CoQ) biosynthesis through the mevalonate pathway works in synergy with the proteasome inhibitor bortezomib (BTZ) in MM. We show that gene expression signatures relating to the mitochondrial tricarboxylic acid (TCA) cycle and electron transport chain (ETC) predispose to clinical BTZ resistance and poor prognosis in MM patients. Mechanistically, BTZ-resistant cells show increased activity of glutamine-driven TCA cycle and oxidative phosphorylation, together with an increased vulnerability towards ETC inhibition. Moreover, BTZ resistance is accompanied by high levels of the mitochondrial electron carrier CoQ, while the mevalonate pathway inhibitor simvastatin increases cell death and decreases CoQ levels, specifically in BTZ-resistant cells. Both in vitro and in vivo, simvastatin enhances the effect of bortezomib treatment. Our study links CoQ synthesis to drug resistance in MM and provides a novel avenue for improving BTZ responses through statin-induced inhibition of mitochondrial metabolism.